Big experimenter is watching you! Anonymity and prosocial behavior in the laboratory - Barmettler, Franziska; Fehr, Ernst; Zehnder, Christian (Games and economic behavior, 2012)
Researchers have demonstrated that the presence of people with social preferences has important economic implications. However, the empirical basis of this research relies to a large extent on experiments that do not provide anonymity between experimenter and subject. It has been argued that this lack of experimenter–subject anonymity may create selfish incentives to engage in seemingly other-regarding behavior. If this were the case, these experiments would overestimate the importance of social preferences. Previous studies provide mixed results and methodological differences within and across studies make it difficult to isolate the impact of experimenter–subject anonymity. In this paper we use a novel procedure that allows us to examine the impact of the exact same ceteris-paribus variation in anonymity on behavior in three of the most commonly used games in the social preference literature. We find that the introduction of experimenter–subject anonymity has no significant effect in any of the three games.